Armed conflict and business operations in Sudan: Survey evidence from agri-food processing firms - Kirui, Oliver K.; Siddig, Khalid; Abushama, Hala; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2023)
This study assesses how agri-food processing enterprises have been affected during the first 3 months of the on-going conflict in Sudan between the Sudan Armed Force (SAF) and the Rapid Support Forces (RSF). The food processing and beverage manufacturing sector plays a significant role as a source of food, employment, and value addition in Sudan. Thus, the ensuing conflict will have both direct and indirect negative consequences to livelihoods and food security. We collected data from representatives of food processing and beverage manufacturing companies throughout Sudan via web-based interviews. The findings highlight the immediate implications of the conflict on the agri-food processing and manufacturing sector. The impact of the conflict has immediately extended beyond direct destruction of the infrastructure and equipment of the firms to cause serious negative employment effects. Furthermore, it led to a growing scarcity of the key material inputs/raw materials and an associated spike in the price of these key ingredients to the production processes. We discuss the implications of these findings vis-à-vis the fluid nature of the continuing conflict and propose some options in preparations to rebuilding the agri-food enterprises once the cessation of hostilities and the end of conflict is achieved.